Proposal to Improve the Reusable Urban Waste Management System in Santiago De Surco, Lima, Peru to Increase the Utilization of the District's Treatment Plant - Fernández Villafán, Sebastián Alejandro (2023)
This study proposes an improvement for the reusable waste management system in Santiago de Surco, in a way that it significantly increases the utilization of the treatment plant, which is demonstrated in Arena Simulation Software. First, a diagnosis of the current conditions of the system is carried out to identify opportunities for improvement, followed by a comparison between successful models worldwide. From them, the elements that can be replicated are rescued considering the existing limitations both in the district, as well as in the simulation. Finally, a proposal is made from the combination of initiatives taken from countries with high recycling rates. This proposal is transferred to a simulation model to demonstrate that a significant improvement is achieved.